129k views
2 votes
What is the solution to 2(x - 3) = 2x + 5

User Xeed
by
5.2k points

1 Answer

5 votes

Answer:

X cannot be decided

Explanation:

According to the question,we will start solving the problem by dealing with the bracket first

So let's get to work

2(x-3)=2x+5

Bracket first

2x-6=2x+5

So let's collect like terms

2x-2x=5+6

0=11

Which means the that we can't get the value for x because x has already been eliminated

So to my own understanding there is no definite solution to get the real value of x

I hope you understand

User Eric Lubow
by
5.3k points